The Effectiveness of Passion Fruit Juice Consumption as Pain Reliever for Bruise Trauma in Pencak Silat Athletes - Irawan, Roy Januardi (Jurnal Kesehatan Masyarakat, 2017)
Pencak Silat is a martial art that has a risk of causing micro-trauma due to physical impact. This trauma will stimulate the secretion of prostaglandin, a compound in the body which is a mediator of pain and inflammatory response that promote pain in bruised trauma. Passion fruit contains high level of anti-inflammatory and antioxidant substances. The objective of this study was to understand the effectiveness of passion fruit juice consumption in reducing bruised trauma pain in Pencak Silat athletes of PSHT Belotan Magetan. The research design is a quantitative descriptive with quasi-experimental. The pretest and posttest group of 20 people PSHT Belotan Magetan Pencak Silat athletes with an average age of 13.4 Â± 0.94 years were divided into treatment group (K1) and control group (K0) with 10 subjects respectively. Each treatment group (K1) subject was given the juice twice a day for 10 consecutive days. We used paired sample T-test to assess the mean variance of the group. The result showed that there was a decrease of pain intensity in both the treatment group and the control group. The pain intensity difference assessed by a Bourbonnais Rating Scale in the treatment group showed a significant difference with the t value of 7,216 and a probability value of 0,000, while the control group showed t value of 3,000 and probability value of 0,015. There was a decrease in the athleteâs muscle soreness who were given passion fruit juice twice a day for 10 days. The athleteâs pain intensity was in middle category.